Electrochemical Performance of Li4-xTi5CuxO12 for Lithium Ion Capacitor Applications - Ahmad Sohib; Achmad Subhan; Wahyu Bambang Widayatno; Slamet Priyono; Chairul Hudaya; Ilma Nuroniah; Sherly Novia Sari; Bambang Prihandoko (Widyariset, 2020)
Lithium titanat (LTO) has attracted considerable attention since it has unique characteristics for energy storage application. Doped LTO is one of approach to improve LTO performance. To date, doped LTO performance in full cell lithium ion capacitor has rarely been discussed. This study is aimed to synthesize Cu-doped LTO via solid state reaction and high energy milling and investigate its electrochemical performance in full cell of lithium ion capacitor. Cu-doped LTO is synthesized via solid state method with high energy milling. Diffraction pattern exhibit that Cu-doped LTO has been successfully synthesized even some impurities such as Baddeleyite, ZrO2, and Li2O appear in each sample. Cyclic voltammogram profile of half-cell based Cu-doped LTO shows that the oxidation and reduction peaks are declined due to its impurities contain. electrical resistance of LTO and Cu-doped LTO becomes smaller as increasing dopant contain while charge transfer resistance is higher. Full cell performance of LIC represent that undoped  LTO//Activated carbon shows higher capacitance, namely 430 µFg-1 at specific current of 50 mAg-1than that of 2.5%-Cu-doped LTO//AC holds 15 µFg-1.